Enhanced performance of bimetallic PtCo/MCM-41 catalysts for glycerol oxidation in base-free medium. Issue 18 (15th August 2019) - Yan, Hao; Qin, Hansong; Liang, Wei; Jin, Xin; Zhang, Yashuang; Feng, Xiang; Liu, Yibin; Chen, Xiaobo; Yang, Chaohe
Abstract : Optimizing the electronic coupling in heterogeneous catalysts by tuning metal–metal interactions remains a significant challenge. Abstract : Optimizing the electronic coupling in heterogeneous catalysts by tuning metal–metal interactions remains a significant challenge. Herein, we report unique bimetallic PtCo/MCM-41 catalysts prepared by in situ doping Co species into MCM-41 for selective oxidation of glycerol to glyceric acid in base-free medium. Surface characterization using H2 -TPR, HAADF-STEM, HRTEM, XPS and DFT calculation confirmed that the synergy between Pt and Co significantly improves the catalytic performance. Specifically, decreasing the Si/Co molar ratio up to a point decreases the particle size and improves electron transfer from Co to Pt within the bimetallic nanoparticles, leading to a volcanic-shaped relationship between the Si/Co ratio and the catalytic performance. The PtCo/MCM-41 catalyst with a Si/Co ratio of 200 was found to exhibit superior selectivity for glyceric acid (85.2%), excellent catalytic activity (TOF: 658.6 h −1 ) and stability in base-free medium. The identification of unique active sites at Pt–Co interfaces in this study should assist in the rational design of novel catalytic materials for efficient conversion of bio-derived substrates to value-added products under mild conditions.